THE INFLUENCE OF ARCHITECTURAL STYLES ON FORMATION IN ARCHITECTURAL DESIGN AND FASHION - Тюрікова, Олена; Лозінська, Яна; Бондар, Ольга; Нестеренко, Діана (SWorldJournal, 2025)
The article explores the impact of architectural styles on the processes of form generation in architectural design and fashion. Through the analysis of stylistically distinct architectural landmarks of the past, the study identifies formal characteristic